Uji Teknis Alat Pengolahan Minyak Kelapa Skala Kelompok Tani / Technical Test of Coconut Oil Machinary on Farmer Group Scale - Abner Lay; Steivie Karouw (Buletin Palma, 2006)
Coconut processing machine for farmer level, was tested in Engineering processing workshop of ICOPRI  Manado, on January 2006. The coconut processing machines were two operation units, namely fresh coconut grinder and coconut milk presser. Tested matterial was Coconut Mapanget Tall.  The observation was done on constraction, operation system, and machine performances.  The results showed that coconut grinder and coconut presser were compactly designed, with partial operation system.  Machine was operated by single rotary  motor  of 7 Hp, 2600 rpm as diesel engine.  Processing system rolling among unit operations,  done by two operators.  Capacity of the coconut fresh grinder is 360 coconut nut/hour and coconut milk presser  is 375 coconut nut/hour. Oil recovery is 15% and oil efficiency extraction about 44.3 %. Use of the  coconut processing machine for farmer level would support  the development of coconut diversification products and provide labour in the villages.  RINGKASANPengujian alat pengolahan minyak kelapa skala kelompok tani dilakukan di Bengkel Rekayasa Alat Pengolahan Balitka, bulan Januari 2006. Alat yang diuji terdiri dari unit pemarut kelapa dan unit pengepres santan. Bahan uji yang digunakan adalah kelapa dalam Mapanget. Pengamatan yang dilakukan, meliputi: konstruksi alat, sistem operasi dan kinerja alat. Hasil pengamatan menunjukkan bahwa unit pemarut dan unit pengepres konstruksinya sederhana dan dirancang secara gabungan dengan sistem proses parsial. Menggunakan motor penggerak tunggal yakni motor diesel dengan daya 7 Hp; 2600 rpm. Sistem operasi alat secara bergantian antar unit operasi, penanganannya oleh dua operator. Kapasitas olah unit pemarut dan unit pengepres masing-masing 360 dan 375 butir kelapa/jam. Rendemen hasil minyak 15% dan efisiensi ekstraksi minyak sebesar 44.3%. Penggunaan alat pengolahan kelapa ini, akan menunjang pengembangan diversifikasi produk kelapa dan perluasan lapangan kerja dipedesaan.